2020
DOI: 10.24349/acarologia/20204396
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and biological features of Typhlodromus (Anthoseius) recki (Acari: Phytoseiidae) on Tetranychus urticae, T. evansi (Acari: Tetranychidae) and Aculops lycopersici (Acari: Eriophyidae)

Abstract: The mite family Phytoseiidae contains predatory species used in biological control. However, among the 2,521 valid species, only a few are presently considered for pest management. The study focuses on a species, frequently observed in agrosystems, but whose biology is almost totally unknown: Typhlodromus (Anthoseius) recki. The objectives were to assess its distribution and to determine under laboratory conditions: (i) the development of three populations fed on three tomato pests (Tetranychus urticae, T. eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Three species were particularly highly reported-Typhlodromus (Typhlodromus) athiasae Athias-Henriot, essentially occuring in Israel; Phytoseiulus persimilis Athias-Henriot, because of mass-release in tomato crops of this commercialised species; and Typhlodromus (Anthoseius) recki Wainstein widely reported all over Europe (Tixier et al 2020a, Demite et al 2024. Recent laboratory studies have shown that the latter species is able to feed on tomato mite pests and is therefore considered a promising predator (Tixier et al 2020b, Ersin et al 2021). The rst objective of this study is to assess the ability of this species to disperse ambulatory along the tomato stem, considering six varieties of Solanum lycopersicum, S. peruvianum and S. cheesmaniae with contrasting types and densities of trichomes on stem.…”
Section: Introductionmentioning
confidence: 99%
“…Three species were particularly highly reported-Typhlodromus (Typhlodromus) athiasae Athias-Henriot, essentially occuring in Israel; Phytoseiulus persimilis Athias-Henriot, because of mass-release in tomato crops of this commercialised species; and Typhlodromus (Anthoseius) recki Wainstein widely reported all over Europe (Tixier et al 2020a, Demite et al 2024. Recent laboratory studies have shown that the latter species is able to feed on tomato mite pests and is therefore considered a promising predator (Tixier et al 2020b, Ersin et al 2021). The rst objective of this study is to assess the ability of this species to disperse ambulatory along the tomato stem, considering six varieties of Solanum lycopersicum, S. peruvianum and S. cheesmaniae with contrasting types and densities of trichomes on stem.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported potential predator species, some belonging to the Iolinidae family, against A. lycopersici. 13,16,17,18,19,20 Typhlodromus recki (Wainstein) (Phytoseiidae) had good results in vitro but still needs to be assessed in vivo. 19 Homeopronematus anconai (Baker) (Iolinidae) and Neoseiulus fallacis (Garman) (Phytoseiidae) were compared and both provided good results against A. lycopersici.…”
Section: Introductionmentioning
confidence: 99%
“…13,16,17,18,19,20 Typhlodromus recki (Wainstein) (Phytoseiidae) had good results in vitro but still needs to be assessed in vivo. 19 Homeopronematus anconai (Baker) (Iolinidae) and Neoseiulus fallacis (Garman) (Phytoseiidae) were compared and both provided good results against A. lycopersici. 13,20 N. fallacis has been judged as having more potential for biological control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation